Hypoxia caused by unilateral nasal obstruction decreases mandibular density in rats through inhibition of Cyp1a1 expression - Xu, Yixin; Wang, Yixin; Xiao, Hui; Li, Yongming (Journal of oral pathology & medicine, 2023)
Background Oral breathing has an important impact on morphology and bone mineral density (BMD) in a mandible. This study aimed to investigate the hub genes and mechanism regulating the mandibular BMD decrease induced by nasal obstruction. Methods A unilateral nasal obstruction model was established in 1‐week‐old Wistar rats by electrocautery obstruction. BMD of the mandible was determined by micro‐computed tomography. Transcriptome analysis was performed to identify differentially expressed genes (DEGs). Hub genes were identified by building protein–protein interaction network and verified by western blot. A hypoxic cell model was established in bone marrow mesenchymal stem cells (BMSCs) by using CoCl2. The expression of hypoxia‐inducible factor‐1α (HIF‐1α), NF‐kB ligand–receptor activator (RANKL), osteoprotegerin (OPG), and Cyp1a1 was detected by western blot. Results The mandibular BMD of rats in the unilateral nasal obstruction group was significantly decreased. A total of 38 DEGs were identified in nasal obstruction rats compared with normal rats. A ratio of RANKL/OPG in the mandible was elevated by nasal obstruction, while the Cyp1a1 was decreased. In vitro, the HIF‐1α expression and RANKL/OPG ratio were upregulated by hypoxia while the Cyp1a1 expression was decreased. Pretreatment with Cyp1a1 activator, FICZ, could increase the expression of Cyp1a1 while attenuating the activation of HIF‐1α and RANKL. Conclusion Respiratory changes caused by nasal obstruction contribute to the decrease in Cyp1a1 expression in the mandible of juvenile rats, which is associated with disturbances in bone homeostasis controlled by the RANKL/OPG ratio.